PEMANFAATAN RINFODOCS SEBAGAI MEDIA PENYUSUNAN DRAFT LAPORAN DALAM PROSES BIMBINGAN TUGAS AKHIR PADA PERGURUAN TINGGI - Ary Budi Warsito; Muhamad Yusup; Erlita Rasdiana (Universitas Raharja, 2015)
Learning in Higher Education System is identical to a conventional manner. This is evident from the way the students in final report. In the process of guidance, the students are still accustomed to the draft report in the form of a printout of the Lecturer. Lecturer then perform correction on the draft report printed sheet, so if there are errors in the writing of the report, the student is required to revise and reprint subsequently submitted to the Lecturer for further corrected. This is very inefficient in the guidance process, due to the use of paper that is not a little, due to the printout draft report before and after the revision. Final report guidance process is the same as running in Raharja University. Then to support that learning systems can make it easier for students and the Lecturer is to utilize RinfoDocs as a medium to support the process guidance Final report. RinfoDocs is one feature in RinfoDrive provided by Rinfo. While Rinfo is a platform using Google’s Gmail service provided exclusively by the Pribadi Raharja (Civitas Academic). Because using the Google email platform. With the RinfoDocs learning process can be done online because it can be done anywhere and anytime. Through the use of RinfoDocs expected to facilitate the process of drafting the final report guidance on the college.